Rekonstruksi Ittjāh al-Adabī al-Ijtimāʻī: Menafsirkan al-Qur’an dari Perspektif Inklusif - Basri, Basri; Nurul Yaqin, M. Zubad; Muhammad, Muhammad; Walkaromah, Naylul Izzah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This article examines the social literary approach to interpreting the Qur'an. The social literary approach is perceived as a portrayal of the social and cultural milieu surrounding the commentator. Although this approach appears more attuned to society, it transpires that the social literary approach employed by commentators exhibits less affinity towards contemporary culture, traditions, and politics in Indonesia. This is because commentators place greater emphasis on imparting advice and reminders for adhering to Islamic principles. Present-day developments are constrained to conform to classical interpretations, with dissenting interpretations being deemed erroneous. The lack of flexibility, accommodation, and adaptability to local traditions and culture is evident in the interpretation of the Qur'an. The current phenomenon in Indonesia entails endeavors to realize religious moderation to uphold the unity, harmony, and peace of all Indonesian citizens. This pursuit of religious moderation necessitates new interpretations that are adaptable and not rigidly bound to culture and differences. Reconstructing the social literary approach is a necessary measure to achieve this goal. The methodology employed in this article is qualitative-interpretive and draws upon acculturation theory, which underscores cultural diversity. The reconstructed approach outlined in this article advocates for an interpretation of the Qur'an that integrates with culture and tradition, rather than imposing itself upon them. Three key considerations are delineated for actualizing the social literary approach in interpreting the Qur'an: observing phenomena, accounting for spatial and temporal contexts, and prioritizing the public good.